2022
DOI: 10.1111/cts.13317
|View full text |Cite
|
Sign up to set email alerts
|

Safety, pharmacokinetics and target engagement of novel RIPK1 inhibitor SAR443060 (DNL747) for neurodegenerative disorders: Randomized, placebo‐controlled, double‐blind phase I/Ib studies in healthy subjects and patients

Abstract: RIPK1 is a master regulator of inflammatory signaling and cell death and increased RIPK1 activity is observed in human diseases, including Alzheimer's disease (AD) and amyotrophic lateral sclerosis (ALS). RIPK1 inhibition has been shown to protect against cell death in a range of preclinical cellular and animal models of diseases. SAR443060 (previously DNL747) is a selective, orally bioavailable, central nervous system (CNS)-penetrant, small-molecule, reversible inhibitor of RIPK1. In three early-stage clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
3
43
0
Order By: Relevance
“…SAR443820 is an inhibitor of receptor-interacting serine/threonine protein kinase 1 (RIPK1), an intracellular protein that is activated by tumor necrosis factor alpha (TNF‐α) through TNF receptor 1 and can induce neuroinflammation by increasing microglial activity and cytokine release and mediate neuronal cell death through apoptosis and necroptosis ( Yuan et al, 2019 ; Vissers et al, 2022 ). The inhibition of RIPK1 was found to block oligodendrocyte death, microglial inflammation and axonal degeneration in both SOD1G93A mice and Optn−/− mice ( Yuan et al, 2019 ).…”
Section: Drugsmentioning
confidence: 99%
“…SAR443820 is an inhibitor of receptor-interacting serine/threonine protein kinase 1 (RIPK1), an intracellular protein that is activated by tumor necrosis factor alpha (TNF‐α) through TNF receptor 1 and can induce neuroinflammation by increasing microglial activity and cytokine release and mediate neuronal cell death through apoptosis and necroptosis ( Yuan et al, 2019 ; Vissers et al, 2022 ). The inhibition of RIPK1 was found to block oligodendrocyte death, microglial inflammation and axonal degeneration in both SOD1G93A mice and Optn−/− mice ( Yuan et al, 2019 ).…”
Section: Drugsmentioning
confidence: 99%
“…In vivo studies have shown beneficial effects of RIPK1 inhibitors in myocardial ischemia and reperfusion injury settings 12–14 . A few RIPK1 inhibitors have progressed to human clinical trials for the treatment of inflammatory and central nervous system (CNS) diseases 15–20 …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] A few RIPK1 inhibitors have progressed to human clinical trials for the treatment of inflammatory and central nervous system (CNS) diseases. [15][16][17][18][19][20] Here, we report results from the phase I first-inhuman study of GFH312 (Clini calTr ials.gov Identifier: NCT04676711), a highly selective small molecule targeting RIPK1 with potent in vitro inhibition of human RIPK1 kinase activity, with a 50% inhibitory concentration (IC 50 ) of 40 nM, that has shown potent anti-necroptosis effects in multiple cell line models, and protective effects in neurological and inflammatory disease models (F. Zhou, F. Xie, and Z. Huo, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Structurally RIPK1 kinase has a hydrophobic pocket associated with its activation segment that is highly amenable for developing small molecule inhibitors which can stabilize its inactive conformation and allows BBB passage ( 19 22 ). Human clinical trials of small molecule RIPK1 inhibitors have demonstrated safety of targeting RIPK1 kinase ( 23 25 ). These studies demonstrated the feasibility and safety of targeting RIPK1 in humans.…”
Section: Introductionmentioning
confidence: 99%